CircPDE4B inhibits retinal pathological angiogenesis via promoting degradation of HIF‐1α though targeting miR‐181c. Issue 9 (25th June 2020) - Deng, Yan; Li, Shurong; Li, Shuanglian; Yu, Chunhong; Huang, Dan; Chen, Hongping; Yin, Xiaolong
Abstract: Retinopathy of prematurity is a major cause of childhood blindness worldwide. Hence, exploring the proper treatment methods is a must in tacking this disease. qRT‐PCR and western blot were used to detect the expression of genes and proteins, respectively. The proliferation of human retinal vascular endothelial cells (HRECs) was ensured by MTT assay. The luciferase activity was measured through luciferase assay. The inverted phase‐contrast light microscope was used to observe the formation of a vascular tube. In the present study, our data demonstrated that circPDE4B was downregulated, while hypoxia‐inducible factor‐1α (HIF‐1α) and VEGFA were upregulated in the retinopathy of prematurity model in vitro and in vivo. CircPDE4B increasing remarkably inhibited the expression of HIF‐1α and VEGFA in hypoxia‐induced HRECs and subsequent repressed cell proliferation and pathological angiogenesis. We further found that miR‐181c suppressed the expression of von Hippel–Lindau (VHL), while circPDE4B could promote VHL expression via binding to miR‐181c. Finally, our results revealed that circPDE4B inhibited the expression of VEGFA and pathological angiogenesis via facilitating VHL‐mediated ubiquitin degradation of HIF‐1α. In conclusion, circPDE4B suppressed the expression of VEGFA and pathological angiogenesis via promoting VHL‐mediated ubiquitin degradation of HIF‐1α through binding to miR‐181c. Our study indicated that circPDE4B might be an effective therapeutic target of retinopathy of prematurity.